DEMOKRASI DALAM GENGGAMAN PARA PEMBURU RENTE (STUDI KASUS ASAHAN SUMATERA UTARA) - Desi Rahmawati (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Vedi R. Hadiz’s concern on New Order’s strong and durable influence to current politics (old predatory interest/ durable capitalist oligarchy) is quite interesting. His thesis that Indonesian democracy is flawed due to old predatory interest rooted in New Order tends to be problematic in some ways as it ignores context as well as actors’ contribution. This writing, therefore, argues that Hadiz’s structural explanation does not work in all localities, even North Sumatra—his main research locus. Rather, it argues that explaining the correlation between democracy and predatory interest (rent seeking), one necessarily paying attention to specific logic (“abstract structure”) works in localities and actors’ consideration upon it.